Bilirubin and oxidative stress in term and preterm infants. (2nd January 2019) - Dani, Carlo; Poggi, Chiara; Pratesi, Simone
Abstract: Hyperbilirubinemia is the most frequent clinical problem neonatologists must deal with during the newborn period. It has been suggested that bilirubin is involved in the balance between antioxidant and pro-oxidant agents due to its antioxidant properties. However, the relevance of these effects in vivo in term and preterm infants is still debated. We performed a literature review of studies that investigated the association between total serum bilirubin (TSB) and oxidative stress in newborn infants. We found that studies in term infants give contradictory results, while studies in preterm infants suggest that the TSB increase is associated with an oxidative stress increase due to concurrent factors other than bilirubin level, such as heme oxygenase (HO) activity. Moreover, it could be speculated that low physiologic TSB values are associated with antioxidant effects, while high pathologic TSB values are associated with pro-oxidant effects. Literature data do not allow the establishment of whether if the antioxidant properties of bilirubin are important from a clinical point of view and can affect the outcome in ill infants.